The Impact of the Free Fire Online Game on Language Attitudes Elementary School Students - Hamila Hamila; Edhy Rustan (IAIN Palopo, 2023)
Playing online games has become a habit, including among elementary school students currently. In addition to entertainment, online games are often used as a means of learning. This study aims to determine the impact of free-fire online games on students' language attitudes. This research was designed in a qualitative descriptive form. The research was conducted on students, teachers, and parents of fourth-grade students at SD Negeri 31 Salotellue, Palopo City. Data was collected through observation and interviews. Data analysis was carried out qualitatively by following the Miles and Huberman model. The results of this study indicate that students are active users of free-fire online games using Android devices with a duration of 2-3 hours a day. Students' language attitudes from playing Free Fire online games can be seen using less polite and careful language choices. Changes in students' language attitudes after using the free-fire online game for a long time are indicated by using pejorative language, addiction, emotional changes, interest in learning and lack of interaction. On the other hand, students also get a second language, English, in the form of several vocabulary words used in daily activities.